A Study to Investigate the Viscosity Effect on Micro-Confined Fluids Flow in Tight Formations Considering Fluid–Solid Interaction - Chen, Mingqiang; Li, Qingping; Cheng, Linsong; Wang, Xiukun; Lyu, Chaohui; Fan, Qi (Frontiers in Earth Science, 2021)
Understanding different fluids flow behavior confined in micro scales has tremendous significance in the development of tight oil reservoirs. In this paper, a novel semi-empirical model for different confined fluids flow based on the concept of boundary layer thickness, caused by fluid-solid interaction, is proposed. Micro-tube experiments are carried out to verify the novel model. After the validation, viscosity effect on the flow rate and Poiseuille number considering fluid-solid interaction is investigated. Furthermore, the novel model is incorporated into unstructured networks with anisotropy to study the viscosity effect on pore scale flow in tight formations respectively under the conditions of different displacement pressure gradients, different aspect ratios (ratio of the pore radius to the connecting throat radius) as well as different coordination numbers. Results show that viscosity effect on the flow rate and Poiseuille number after considering fluid-solid interaction induces a great deviation from that in conventional fluids flow. The absolute permeability is not just a parameter related to pore structures but also depends on fluid viscosity. The study provides an effective model in modelling different confined fluids flow in micro scales and lays a good foundation for studying fluids flow in tight formations.